Eye lens diameter and weight as an age indicator in two sparid fishes off Benghazi coasts, Libya - Al Hassan, L A J; El Toumy, F F; El Silini, O A; El Burasi, H (Indian Journal of Fisheries, 2011)
The eye lens diameter and weight in the sparid fishes, Boops boops and Diplodus annularis, were tested for their vahdity as age indicators. The results showed that the eye lens diameter in B. boops could be used to differentiate fishes in their 2"’’ and 3"’ years of life from those of the 1*" and 2"’’ year classes. On the other hand, in D. annularis, this technique succeeded to differentiate S"’ and 2"^ year classes. Eye lens weight technique proved well to differentiate fishes in the 0 and 1 year class of B. boops from the remaining age groups. On the other hand, it proves not a good criterion to differentiate among the fish age groups of D. annularis except for l’’’^ and 3’’’’ year classes.